(1+s^2)^-1 = (1+s^2)^0 - (1+s^2)^-1 = 1/ 1+s^2
times s^2
= s^2/ 1+ s^2
:O
correct me if I'm wrong
r(s)= ((1+s^2)^-1, root 2 s(1+s^2)^-1, 1- (1+s^2)^-1
I understand this simplification up to a point:
r(s)= 1+s^2)^-1 (1, root2 s, s^2) (green i understand, red i dont)
the (1+s^2)^-1 substitutes nicely for the first 2 sections, but what is the algebra required for the last part?
I mean s^2 multiplied by (1+s^2)^-1 is equal to 1- (1+s^2)^-1 but I cannot work out how to derive this.
Can anyone help please?
Ni hao! and thanks for the help.
your message:
(1+s^2)^-1 = 1/ 1+s^2
times s^2
= s^2/ 1+ s^2
---
(1+s^2)^-1 = 1/ 1+s^2 - yes understand that
times s^2 - why?
how did you know to multiply by s^2 at the end?
What were the algebraic steps on the run up to that answer?
feichang ganxing =]